Reward-seeking behaviors moderate the association between early life adversity and anhedonia 12 months later - Tran, Mai-Lan; Rao, Uma; Bower, Julienne; Fuligni, Andrew; Kuhlman, Kate Ryan (Frontiers in Behavioral Neuroscience, 2025)
Approximately 20% of adolescents report experiencing anhedonia, conferring high risk for the onset of adolescent depression. Early life adversity (ELA) is associated with anhedonia, and individual differences in reward motivation may inform this association. The current study examined whether reward-seeking behaviors moderated the prospective association between ELA and anhedonia 12-months later among adolescents. During a baseline visit, 74 participants, aged 11–17, completed the Balloon Analogue Risk Task (BART) to measure reward-seeking behaviors via adjusted average balloon pumps. Indeed, participation in the BART has been shown to activate the fronto-striatal neural circuits known to subserve reward-seeking. ELA was assessed continuously via parent-report using a 9-item Adverse Childhood Experiences questionnaire, with scores reflecting cumulative exposures to adversity prior to enrollment; interaction effects were subsequently probed at low, average, and high values for interpretation. At baseline and 12-months later, participants completed the anhedonia subscale within the Reynolds Adolescent Depression Scale 2nd Edition. Adolescents with greater ELA reported more anhedonia 12-months later (b = 0.97, SE = 0.46, p = 0.04), suggesting that ELA confers risk for developing anhedonia. Reward-seeking behavior moderated this association, such that adolescents with more experiences of ELA and low (b = 2.35, SE = 0.61, p < 0.01) and average reward seeking-behavior (b = 0.95, SE = 0.43, p = 0.03), but not high reward-seeking behavior (b = −0.45, SE = 0.60, p = 0.45), were at the greatest risk for increasing severity of anhedonia across the subsequent 12-months. Reward-seeking behaviors may aid in distinguishing which youth with ELA are at risk for depression. Additionally, results from this study may help to inform more specific interventions by increasing reward-seeking behaviors to mitigate the risks of developing anhedonia.